A Highly Stretchable Microsupercapacitor Using Laser‐Induced Graphene/NiO/Co3O4 Electrodes on a Biodegradable Waterborne Polyurethane Substrate. Issue 2 (17th January 2020) - Wang, Wentao; Lu, Longsheng; Xie, Yingxi; Yuan, Wei; Wan, Zhenping; Tang, Yong; Teh, Kwok Siong
Abstract: Constructing microsupercapacitors (MSCs) with an outstanding stretchability is urgent for wearable electronics, and an intrinsic biodegradability is also meaningful. Herein, laser‐induced graphene/NiO/Co3 O4 (NiO/Co3 O4 /LIG) is in situ synthesized on a polyimide (PI) film during laser processing, then the electrodes are transferred to a biodegradable waterborne polyurethane (WPU) substrate to fabricate stretchable MSCs. Experimentally, the as‐prepared stretchable MSCs exhibit an excellent areal capacitance of 2.4 mF cm −2, high capacitance retention of 77.1% at 50% strain, and capacitance degradation of less than 19.8% after 1000 stretching cycles. These desirable properties are mainly attributed to the gradient structure of NiO/Co3 O4 /LIG, the synergistic effect of hybrid NiO/Co3 O4 nanoparticles, and the intensive interface adhesion between the electrodes and WPU. Interestingly, the robust function of stretchable MSCs is further presented by using them to power a microsensor and assembling them with triboelectric nanogenerators to generate power from mechanical contact with skin, which makes the stretchable MSCs promising as a sustainable driving source for wearable electronics. Abstract : A simple, green, and environmentally friendly fabrication route is used to prepare stretchable microsupercapacitors (MSCs) on a biodegradable waterborne polyurethane (WPU) substrate, which exhibits an excellent electrochemical stability even under extremely complex deformations. The stretchable MSCs connected in series could be utilized as power source to drive a wearable pressure sensor and when assembled with triboelectric nanogenerators, could generate power from human motion.